The Cultural Diversity of Muslim Convicts and the Expectations of Penitentiary Practices in Eastern European Countries - Urbanek, Arkadiusz; Gandecka, Kamila (Acta Paedagogica Vilnensia, 2016)
The study presents tendencies in dealing with Muslims that became apparent in Poland, Lithuania and Czech Republic. The research was conducted among prison staff members and demonstrantes their reactions to expectations of Muslim convicts. Also, they attempt to answer the question of sanctioning such claims. An attempt to identify the source of claims is necessary for developing a clear position in the field of penitentiary practice. Thus, it can also influence the creation of unequivocal guidelines for dealing with Muslim convicts.
Keywords: prison; foreign national; penal policy; multiculturalism